Towards an international university. A professorship at The Franz Joseph University (Cluj-Napoca) in 1901 - Ildikó P. Varga (Revista Română pentru Studii Baltice şi Nordice, 2014)
The Franz Joseph University in Kolozsvár (now Cluj-Napoca, Romania) was the second modern university in the Kingdom of Hungary and it was founded in 1872. This paper presents a micro-historical investigation of a case from 1901, when the University considered inviting a Finnish linguist to the Department of Hungarian and Comparative Linguistics after the death of the Hungarian Jewish Professor Ignác Halász. The study sheds light on the arguments made to justify the need for a foreign professor and why this plan was not realized and on the role played by Emil Nestor Setälä, the professor of Finnish language and literature at the University of Helsinki, in the appointment process. The study is based on the personal correspondence of one of the candidates, Béla Vikár and the official documents of the University.